Power detection for frequency selective mitigation of pulsed interference - Hirschbeck, Martin; Huber, Johannes (SCC 2015 - 10th International ITG Conference on Systems, Communications and Coding, 2019)
Radio communication systems often suffer from impulsive interference. L-band Digital Aeronautical Communication System 1 (L-DACS 1) which is based on Orthogonal Frequency Divison Multiplexing (OFDM) is one example because its spectrum is located within bands allocated for the impulsive Distance Measuring Equipment (DME). In this paper, a power detection scheme for two frequency selective interference mitigation approaches is proposed and optimal thresholds are investigated for the detection and mitigation of DME at an L-DACS 1 receiver. In addition, optimal parameters for these two mitigation approaches are investigated.
CRIS-Team Scopus Importer:2019-10-22
Keywords: DME; Filter bank; Impulsive interference; Impulsive noise; LDACS; OFDM; Power detection; Pulse blanking